Biodegradability of oil palm cellulose-based bioplastics. (August 2018) - Isroi,; Rahman, A; Syamsu, K
Abstract: This study investigated biodegradation of the bioplastic composite based on oil palm cellulose in plantation soil as natural inoculum. The biodegradation rate was evaluated as carbon dioxide released during the biodegradation test. Biodegradation test of the bioplastic compared with starch-based bioplastic and conventional plastic samples were conducted in the glass jar for 45 days. The carbon dioxide generated from the biodegradation process absorbed by 0.1 N sodium hydroxide solutions. The carbon dioxide was titrated with 0.1 N HCl and using phenolphthalein followed by methyl orange as indicator. Biodegradation rate of the bioplastic was 0.1082 mg CO2 /day and total carbon dioxide for 45 days was 8.8mg. Biodegradation rate of the starch-based bioplastic was higher than the oil palm bioplastic that is 0.157 mg CO2 /day. There was no carbon dioxide released from the conventional plastic during the test. By calculation, total degradation of the bioplastic samples were 254 days and 207 days for the oil palm bioplastic and the starch-based bioplastic, respectively.